Good university governance: budgeting participation and internal control / Rulyanti Susi Wardhani ... [et al.] - Wardhani, Rulyanti Susi; Marwa, Taufiq; Fuadah, LukLuk; Siddik, Saadah; Awaluddin, Murtiadi (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2019)
The purpose of this study was to examine the simultaneous and partial effects of budgeting participation and internal control on good university governance at Bangka Belitung University and State Manufacturing Polytechnic of Bangka Belitung Islands, Indonesia. Data collection used a saturated sampling method of 485 consisting of all employees and lecturers at the two colleges. Estimation models were built based on previous research studies and the Agency Theory. Data analysis techniques used multiple regression analysis along with testing classical assumptions using a Likert scale on primary data. The results of the study showed that budgetary participation and internal control have a positive and significant effect on good university governance both simultaneously and partially, where internal control is the dominant variable influencing good university governance. This illustrates the alignment of findings with the Agency Theory. The implications for the future are that the Bangka Belitung University and the State Manufacturing Polytechnic continue to pay attention to internal control to create a resonance of good university governance towards the internationalization of higher education. In this study only two variables were used that affect good university governance. Other influences also play a role in the improvement including audit committees, organizational culture, and organizational communication climate that can be addressed by future researchers.